The Research of Comparative Characteristics and Functional Features of the Co-integration of Technological Innovations and business Activity and their Impact on the Formation of Macroeconomic Dynamics - B. J. Matrizaev (Финансы: теория и практика)
The subject of the study is the causal relationship between the co-integration of technological innovations and business activity, and their impact on the formation of macroeconomic dynamics in the short and long-term. The purpose of the paper is to propose a comprehensive approach to determining the conditions for the co-integration of technological innovations and business activity for their subsequent stimulation of economic growth. The practical examination of the impact of changes in the dynamics of complex indicators of creative development and commercial activity on economic growth is the research’s scientific contribution and novelty. Using vector error correction models, modular root testing models and other econometric methods, the author demonstrated that both business activity and innovation stimulate economic growth in the long-term. In the short-term, there are strong causal relationships, but they are not always homogeneous. The main conclusion is the fact that the results obtained by the author confirm the correctness of using the approach of determining the order of integration and the presence/absence of co-integration between indicators of innovative development, business activity and economic growth. The summary results confirm the existence of a close long-term equilibrium relationship between innovation, business activity and economic growth.